Analysis Of Learning Methods Of Activities In MTs Darul Huda - Chairani Amalia (Al-Ulum: Jurnal Pendidikan Islam, 2023)
This study aims to describe what methods are used in the learning process of aqidah morals at MTs Darul Huda. This study uses a qualitative approach to data collection techniques in this study using observation, interviews and documentation. Based on the observations I made with the Aqidah Akhlak teacher at MTs Darul Huda school, information was obtained that the teacher only used the lecture method when teaching. once another learning method that needs to be applied by a teacher to be able to create a different atmosphere can be more easily understood and understood by students.